2020
DOI: 10.1111/jocs.14470
|View full text |Cite
|
Sign up to set email alerts
|

Effects and outcomes of cardiac surgery in patients with cardiometabolic syndrome

Abstract: Introduction Cardiometabolic syndrome (CMS) is diabetes mellitus (or insulin resistance) plus any two of the following risk factors: hypertension, obesity, and hyperlipidemia. The correlation of metabolic syndrome with cardiovascular disease and the increase in the prevalence of patients with risk factors have solidified the importance of continued focus on metabolic syndrome. We retrospectively evaluated single‐center data to determine if there is an association between CMS and outcomes. Methods The local Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…We did not assess therapy for DM and CAD, pre‐procedure glucose control, or evidence of end organ damage from either DM or CAD. Cardiometabolic syndrome with DM and obesity is associated with worsened outcomes after coronary artery bypass surgery 31 . In our cohort, BMI was not significantly different between those with or without complications but obesity was not commonly present.…”
Section: Discussioncontrasting
confidence: 45%
“…We did not assess therapy for DM and CAD, pre‐procedure glucose control, or evidence of end organ damage from either DM or CAD. Cardiometabolic syndrome with DM and obesity is associated with worsened outcomes after coronary artery bypass surgery 31 . In our cohort, BMI was not significantly different between those with or without complications but obesity was not commonly present.…”
Section: Discussioncontrasting
confidence: 45%
“…Across these studies, a total of 333 488 patients with MetS underwent surgery versus 1 449 817 surgical patients without MetS. We found fifteen of 44 studies reported an increased risk of mortality across a range of surgical types including bariatric 39 , 43 , 57 , cardiac 19 , 42 , ear, nose, and throat (ENT) 35 , emergency 31 , endocrine 59 , 84 , gastrointestinal 40 , hepatobiliary 23 , 33 , 34 , neurosurgery 49 , and orthopaedic 47 . Twenty-five studies considered for meta-analysis found no association with 30-day mortality between MetS and non-MetS patients across a wide range of surgical types.…”
Section: Resultsmentioning
confidence: 97%
“…Inclusion and Exclusion Criteria). The most commonly reported types of surgery were orthopaedic (22%) 5 , 6 , 15 , 26 , 27 , 29 , 46 48 , 67 , 72 , 73 , 75 , 78 , cardiac (21%) 19 , 20 , 37 , 38 , 41 , 42 , 50 , 51 , 54 , 63 , 64 , 69 , 76 , vascular (13%) 4 , 24 , 53 , 62 , 65 , 68 , 70 , 79 , hepatobiliary (11%) 50 56 , gastroenterology (6%) 57 60 , bariatric (5%) 39 , 43 , 57 , urology (5%) 21 , 58 , 74 , and plastics (5%) 52 , 56 , 77 (see Table 3 . Included Studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients after coronary artery bypass grafting with special reference to cardiometabolic syndrome, exercise and sleep I have read with great interest by Zapata et al, 1 in which the authors evaluated the effects and outcomes of coronary artery bypass graft (CABG) in patients with cardiometabolic syndrome (CMS). The risk of CMS for long-term survival significantly increased, which might be related to comorbidities by CMS.…”
mentioning
confidence: 99%